Should anti-CGRP monoclonal antibodies always be the drug of first choice for migraine prophylaxis in Brazil? - a pharmacoeconomic study - Pelliciari, Davy Henrique Sousa; Reis, Caio Ricco Alves; Bordini, Carlos Alberto (Headache Medicine, 2024)
Efficacy (success of therapy under ideal conditions), efficiency (the relationship between the costs and outcomes of a specific intervention), and effectiveness (the balance between efficacy and efficiency in clinical practice) are measures used to evaluate health interventions. Thus, in private practice and the public health system, the knowledge of these pharmacoeconomic data should influence the appropriate treatment choice. Migraine prophylaxis falls within this context. Traditional medications are available in the public health system, while galcanezumab is not routinely available. The present study aims to analyze the efficacy and effectiveness of galcanezumab and traditional therapeutic alternatives (amitriptyline, divalproex sodium, and topiramate). Efficacy data were obtained from the relevant literature (PubMed) and cost values from the ABCFarma magazine. The economic impact analysis considered the cost of living for an economically active adult in Brazil based on the Brazilian Institute of Geography and Statistics (Instituto Brasileiro de Geografia e Estatística, IBGE) and the Institute for Applied Economic Research (Instituto de Pesquisa Econômica Aplicada, IPEA). Efficacy: amitriptyline: 40%; divalproex sodium: 30%; topiramate: 31%; galcanezumab: 50%. Their annual costs were: amitriptyline R 240.00; sodium divalproate R 876.00; topiramate R 600.00; galcanezumab R 13,992.00. Efficiency: amitriptyline 200%; divalproex sodium 41.1%; topiramate 62%; galcanezumab 4%. Ultimately, effectiveness is amitriptyline 120%; divalproex sodium 35.7%; topiramate 46.5%; galcanezumab 27%. Galcanezumab is the most effective; however, in a broader analysis, where payers, availability, and patient conditions are considered, evaluating efficacy alone may not be feasible in practical contexts and, therefore, anti-CGRP antibodies will not always be the first-line medications in migraine prophylaxis.